Molecular phylogeny of the "salty" Liolaemus species (Reptilia: Squamata): anomalus group, endemic of the Argentina Monte Desert - Morando, Mariana (2021)
In Argentina, the Monte ecoregion extends for more than 2,000 km from NW Argentina to borealPatagonia, and includes many salt-pans and barren flatlands colonized by the monophyleticLiolaemus anomalus group that includes seven species. Some of their external morphologicalcharacteristics and behaviors are very unusual for the genus, and this has led to a complextaxonomic history. The group is very poorly known except for a recent paper with descriptionsof three species and morphological-based phylogenetic hypotheses. Of the four recognizedspecies, two are threatened and one is vulnerable, and while the conservation status of thethree recently described species is unknown, they are suspected to also be under some degreeof threat. We reviewed all georeferenced localities known to produce a distribution map, andsequenced two mitochondrial and four nuclear genes, for representatives of all species. Weinferred a time-calibrated species tree showing that the evolutionary history of this clade occurredentirely during the Pleistocene, with most of the divergences very recent. The climaticand geomorphological changes driving this divergence started during the Great PatagonianGlaciation, initially separating the two northwestern-most distributed species (L. pipanaco +L. pseudoanomalus) from the rest. Given the very recent evolutionary history of the group andtheir unique and conserved morphology, incongruent topologies among datasets are expected; adetailed genome-wide dataset will be needed to fully assess and resolve their speciation history.